From cyberbullying to well‐being: A narrative‐based participatory approach to values‐oriented design for social media. (6th November 2014) - Bowler, Leanne; Knobel, Cory; Mattern, Eleanor
<x xml:space="preserve">Abstract</x> This study looks at mean and cruel online behavior through the lens of design, with the goal of developing positive technologies for youth. Narrative inquiry was used as a research method, allowing two focus groups—one composed of teens and the other of undergraduate students—to map out 4 cyberbullying stories. Each cyberbullying story revealed 2 subplots—the story that "is" (as perceived by these participants) and the story that "could be" (if the participants' design recommendations were embedded in social media). The study resulted in a user‐generated framework for designing affordances on social media sites to counter acts of cyberbullying. Seven emergent design themes are evident in the participants' cyberbullying narratives: design for hesitation, design for consequence, design for empathy, design for personal empowerment, design for fear, design for attention, and design for control and suppression. We conclude with a typological analysis of the values present in the participants' design recommendations, applying Cheng and Fleischman's values framework (2010).